PROFIL MINAT BELAJAR PERSERTA DIDIK DI KELAS VIII SMP N 1 LEMBANG JAYA - Kemala, Niken; Helma, Helma; Kardo, Rici (Center for Research and Community Service (LPPM) University of Abulyatama, 2025)
This research is motivated by the existence of students who are unprepared for learning, late attendance, permission, truancy, activeness in learning, enthusiasm for learning, attention to learning, and interest in learning. The aim of this research is to describe the learning interest profile of students in class VIII SMP N 1 Lembang Jaya seen from the aspects: 1) Feelings of pleasure, 2) Interest, 3) Attention in Learning, and 4) Involvement. This research was conducted using quantitative descriptive methods. The research population was 96 students selected using total sampling technique. The instrument used is a questionnaire. The number of valid questionnaire statements after the trial was 50 items. The data analysis reveals an average percentage of (60,41%) across all aspects, indicating a high category. The results of research on the profile of students' interest in learning in class VIII SMP N 1 Lembang Jaya are seen from the aspects: 1) Feelings of pleasure are in the medium category 2) Interest is in the high category, 3) Attention in learning is in the high category, 4) Engagement is in the high category. Based on the results of this research, it is recommended for guidance and counseling teachers to provide services such as utilizing group guidance and group counseling services, or classical services that are in accordance with what is needed regarding learning interests, then subject teachers are recommended to use a variety of learning methods, for students who have the criteria can increase interest in learning and for future researchers to create an effective guidance service model.